Rola mediów społecznościowych w edukacji – stan obecny i perspektywy rozwoju - Garwol, Katarzyna (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
Artykuł omawia rolę mediów społecznościowych w edukacji. Po krótkim opisie historii rozwoju portali społecznościowych w Polsce i w Europie następuje przegląd badań na temat roli mediów społecznościowych w procesie nauczania oraz omówienie badań własnych autora.

Article describes the role of social media in education. After short description of the development of social services in Poland and in Europe the follows the review of researchconcerning the subject of role of social media in the education process and description of own research.
Role of social media in education – present state and the perspectives of development
Keywords: media społecznościowe; Internet; edukacja; social media; education